Mesenchymal Stem Cells of Dental Origin-Their Potential for Antiinflammatory and Regenerative Actions in Brain and Gut Damage - Földes, Anna; Kádár, Kristóf; Kerémi, Beáta; Zsembery, æ#129;kos; Gyires, Klára; S. Zádori, Zoltan; Varga, Gábor Varga (Current Neuropharmacology, 2016)
Alzheimer’s disease, Parkinson’s disease, traumatic brain and spinal cord injury and neuroinflammatory multiple sclerosis are diverse disorders of the central nervous system. However, they are all characterized by various levels of inappropriate inflammatory/immune response along with tissue destruction. In the gastrointestinal system, inflammatory bowel disease (IBD) is also a consequence of tissue destruction resulting from an uncontrolled inflammation. Interestingly, there are many similarities in the immunopathomechanisms of these CNS disorders and the various forms of IBD. Since it is very hard or impossible to cure them by conventional manner, novel therapeutic approaches such as the use of mesenchymal stem cells, are needed. Mesenchymal stem cells have already been isolated from various tissues including the dental pulp and periodontal ligament. Such cells possess transdifferentiating capabilities for different tissue specific cells to serve as new building blocks for regeneration. But more importantly, they are also potent immunomodulators inhibiting proinflammatory processes and stimulating anti-inflammatory mechanisms. The present review was prepared to compare the immunopathomechanisms of the above mentioned neurodegenerative, neurotraumatic and neuroinflammatory diseases with IBD. Additionally, we considered the potential use of mesenchymal stem cells, especially those from dental origin to treat such disorders. We conceive that such efforts will yield considerable advance in treatment options for central and peripheral disorders related to inflammatory degeneration.
Keywords: Alzheimer’s disease